Bimbingan Keagamaan Pada Perempuan Lanjut Usia Di Panti Jompo Yayasan Al-Yusufiyah Hutaholbung - Magdalena Magdalena; Bestari Endayana (Institut Agama Islam Negeri Padangsidimpuan, 2023)
Religious Guidance is an education system that is developed and encouraged or imbued with Islamic teachings and values. This means that religious guidance is the process of inculcating the values of Islamic education. Elderly women are a group of mothers who are aged 50 and over and live in the Nursing Home of the al-Yusufiyah Hutaholbung Foundation. This study aims to determine the religious life, style of guidance, and implications of religious guidance for elderly women at the al-Yusufiyah Hutabolbung Nursing Home. The research methodology used is qualitative research with anthropological and sociological approaches. The results of the study show that the lives of elderly women at the al-Yusufiyah Foundation Nursing Home are no different from the daily lives of housewives in the family and community. Beautiful conditions like their own homes which are designed in this orphanage make these elderly female mothers feel at home as in their own homes. by the foundation's management in order to achieve the goal of charity until the end of their lives